FEATURES OF STRUCTURAL-PHASE TRANSFORMATIONS IN THIN FILMS OF CRYOVACUUM CONDENSATES OF ETHANOL - Aldiyarov, A.U. (Recent Contributions to Physics, 2008)
The article presents the results of an experimental study of thermally stimulated polyamorphic and polymorphic transformations in cryovacuum condensed ethanol films formed at a substrate temperature T = 16 K. The studies were carried out on a modified cryovacuum spectrophotometer in the frequency range of the IR spectrometer from 4200 to 400 cm-1. New data have been obtained on the temperature ranges of existence of ASE (amorphous solid ethanol), structural glass (SG- structural glass), during ultrafast cooling of a liquid (SCL- supercooled liquid), plastic crystal (PC- plastic crystal), orientationally disordered crystal (ODC- orientationally disordered crystal), fully ordered monoclinic crystal (MC- monoclinic crystal). The data obtained are consistent with modern concepts of transformations in cryovacuum condensates of ethanol.